Overcoming underestimation of the association of excess weight with pancreatic cancer due to prediagnostic weight loss: Umbrella review of systematic reviews, meta-analyses, and pooled-analyses - Mandić, Marko; Pulte, Dianne; Safizadeh, Fatemeh; Niedermaier, Tobias; Hoffmeister, Michael; Brenner, Hermann (Obesity reviews, 2024)
Elevated body mass index (BMI) is linked to increased pancreatic cancer (PC) risk. Cancer-associated weight loss can occur years before the malignancy is diagnosed. This might have led to underestimation of the BMI-PC association. However, it is unknown if and to what extent this issue has been considered in previous epidemiological studies. We searched two databases through February 19, 2024 for systematic reviews, meta-analyses, and pooled analyses examining the BMI-PC association. We extracted information on study design with a special focus on the article's examination of prediagnostic weight loss as a potential source of bias, as well as how included cohort studies addressed this concern. Thirteen review articles, meta-analyses, and pooled analyses were identified. Only five (four pooled analyses, one systematic review) considered prediagnostic weight loss in their analyses. Twenty-four of 32 identified cohort studies reported having excluded initial years of follow-up. However, only 13 studies reported results after such exclusions, and effect estimates generally increased with longer periods of exclusion. We conclude that the association of overweight and obesity with PC risk is likely larger than suggested by published epidemiological evidence. Future studies should pay careful attention to avoid or minimize potential bias resulting from prediagnostic weight loss.